TERAPI HEPARIN TIDAK TERFRAKSI PADA PROSEDUR INTERVENSI KORONER PERKUTAN ELEKTIF - saidi, zaki; Widito, Sasmojo (Jurnal Klinik dan Riset Kesehatan, 2025)
Coronary artery Disease (CAD) occurs due to an imbalance between myocardial oxygen demand and supply due to total or partial blockage of the coronary artery. Occlusion of coronary artery blood vessels in CAD patients requires revascularization to restore blood flow and myocardial perfusion. One of the mechanical revascularization efforts is to perform a percutaneous coronary intervention (PCI) procedure. This technique involves the use of a guided catheter directed to the location of the coronary artery blockage, followed by balloon dilation and stent placement to maintain patency. Blood vessel injury during PCI exposes serine proteases to tissue factor and collagen, stimulating procoagulants that will activate the coagulation cascade. In CAD patients undergoing PCI therapy, periprocedural pharmacotherapy is given in the form of antiplatelet therapy accompanied by intravenous anticoagulants such as unfractionated heparin. Unfractionated heparin produces its main anticoagulant effect by inactivating thrombin and activating factor X (factor Xa) through a mechanism dependent on antithrombin (AT). Intravenous administration of unfractionated heparin in addition to producing anticoagulant effects can also increase the risk of bleeding. In order for the drug to effectively prevent clotting and not cause bleeding, it is necessary to determine the right dose. In connection with this, it is necessary to monitor hemostasis function with optimal Activated Clotting Time (ACT) values ​​to prevent the risk of thrombosis and bleeding in patients undergoing PCI.